The mediating effect of organizational learning on the relationship between lean manufacturing practices and operational performance - Aryarathne, S.P.; Galahitiyawe, N.W.K. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2021)
Manufacturing organizations apply best practices to keep operational expenses at a minimum level without compromising the quality in order to be competitive. Lean manufacturing is such practice adopted by apparel manufacturing firms in Sri Lanka and achieving the expected operational performance has become a challenge due to institutional specific factors. Further, the existing literature is inconclusive and ambiguous on operational performance that resulted from lean practices and paucity of studies explain how lean practices bring performance. Thus, this study argues that lean practices will create operational performance through organizational learning. Accordingly, this study examines the mediating effect of organizational learning on the relationship of lean manufacturing practices to operational performance. A survey is conducted to collect cross sectional data using a self-administered questionnaire. Sample consisted of 386 of managers in the apparel sector in Sri Lanka using simple random sampling technique. Data were analyzed using Structural Equation Modeling (SEM). The results of this study claim a partial mediation of organizational learning on to the impact of lean practices on operational performance. The highest influence for operational performance is through organizational learning (β=0.513) while the direct impact is slightly less ((β=0.200). Study also has tested the criteria of goodness of fitness with absolute, parsimony and incremental fit indices. This study contributes to the existing literature by explaining how lean as a best practice result on operational performance via organizational learning. Thus, practicing managers need to utilize lean practices as a learning mechanism for growth than being taking it as a mere practice. Finally, this study adds value to the Institutional theory by giving a better explanation on when external pressures transform into a practice, how that practice convert into a performance outcome through learning for growth.
Keywords: Lean manufacturing practices (LM), Organizational learning (OL), Operational performances (OP)